Subject-Object Engagement Study in Exhibition Spaces: A Comparison Between Taman Mini Indonesia Indah’s Pavilion and Indonesia Kaya Gallery - Wulandari, Anak Agung Ayu; Ruki, Ulli Aulia; Fajarwati, Ade Ariyani Sari (Bina Nusantara University, 2019)
This research aimed to analyze the engagement between local visitor with objects in a conventional exhibition space and a technology-based exhibition space. The method of this research was a qualitative method with descriptive analysis. The data collection was done in two stages. The first stage was collecting secondary data or desk research. The next stage was the primary data collection using both qualitative and quantitative methods. Data were collected in two exhibition spaces; Riau Islands Province pavilion in Taman Mini Indonesia Indah as conventional exhibition space, and Indonesia Kaya Gallery that was located in the Grand Indonesia shopping mall as a technology-based exhibition space. The research shows visitors’ engagement emerges not only because of the objects itself but also of its surroundings; the path and signage, the lighting design, how the objects displayed and labeled that will create certain engagement with its audience. Technology also gives great help to create subject-object engagement. However, to appreciate and really engaged with the objects, the audience still wants to see real objects and not the digital substituted.